2020
DOI: 10.1097/nnr.0000000000000419
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Infant Well-Being and Self-Reported Distress in Neonatal Nurses

Abstract: Background Infants who are admitted to a neonatal intensive care unit (NICU) may experience significant symptom burden. Parents are often distressed by these symptoms, which can affect their long-term coping and distress. There is limited research examining nurse perceptions of infant well-being (symptoms, suffering, and quality of life [QOL]) and associations with nurse distress. Objective The objective of this descriptive study was to explore associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Perceptions of adverse outcomes appeared to underpin this variation, with statements reflecting the perceived effect of intensive care upon infants and evidence of disability in infants more often prioritized at the extremes of the distribution grid over statements highlighting parental involvement in decision-making. This reflects previous literature identifying that, particularly for neonatal nurses and neonatologists, perceived infant suffering and poor quality of life are distressing when caring for critically ill infants . Studies have consistently highlighted, however, the tendency for obstetricians, midwives, neonatologists, pediatricians, and neonatal nurses to underestimate survival and overestimate severe disability in extremely preterm infants .…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Perceptions of adverse outcomes appeared to underpin this variation, with statements reflecting the perceived effect of intensive care upon infants and evidence of disability in infants more often prioritized at the extremes of the distribution grid over statements highlighting parental involvement in decision-making. This reflects previous literature identifying that, particularly for neonatal nurses and neonatologists, perceived infant suffering and poor quality of life are distressing when caring for critically ill infants . Studies have consistently highlighted, however, the tendency for obstetricians, midwives, neonatologists, pediatricians, and neonatal nurses to underestimate survival and overestimate severe disability in extremely preterm infants .…”
Section: Discussionsupporting
confidence: 75%
“…This reflects previous literature identifying that, particularly for neonatal nurses and neonatologists, perceived infant suffering and poor quality of life are distressing when caring for critically ill infants. 29 , 32 Studies have consistently highlighted, however, the tendency for obstetricians, midwives, neonatologists, pediatricians, and neonatal nurses to underestimate survival and overestimate severe disability in extremely preterm infants. 33 , 34 , 35 , 36 The unpredictable outcomes for these infants creates the potential for misalignment and miscommunication between professionals and between parents and professionals.…”
Section: Discussionmentioning
confidence: 99%
“…The PROMs were administered in several ways, such as through paper-, interview-, tablet-, or computer-based methods at home or in the clinic through a webpage or by e-mail. Furthermore, the expected time needed to answer was mentioned in 13 reports, ranging from 45 s to 2 h [ 54 , 59 61 , 67 , 78 , 84 , 87 , 91 , 97 , 105 , 116 , 133 ].…”
Section: Resultsmentioning
confidence: 99%
“…They believe that the concept of quiet time can reduce the energy consumption of premature infants, protect their neurological development and improve their prognosis. The clinical staff have common sense of care for the special group of high‐risk neonates (Fortney et al, 2020 ). In this interview, we found that medical staff subconsciously want to protect premature infants, do not want them to receive too much stimulation and hope that they can get enough rest and grow up healthily.…”
Section: Discussionmentioning
confidence: 99%